Чорнолакова кераміка з пізньоскіфського городища Булганак - Шапцев, М. С. (Археологія, 2011)
Представлены фрагменты чернолаковой керамики III—II вв. до н. э. из раскопок Булганакского городища в Крыму.
Через привлечение аналогий определено, что наиболее ранние фрагменты относятся к первой четверти III в.
до н. э., что позволяет датировать этим временем возникновение поселения Булганак. Анализ материалов позволяет
предполагать присутствие греческого этнического компонента среди позднескифского населения на раннем
этапе развития Булганакского городища. Имеются также некоторые основания допускать участие Херсонеса Таврического
в основании и жизни данного укрепления. Fragments of black gloss ceramics of the 3rd and the 2nd centuries BC from the excavations of Bulhanak hillfort
in the
Crimea are presented. By the usage of given analogies it was determined that the earliest fragments were dated by the
first quarter of the 3rd c. BC, which allows the author to date the foundation of the hillfort
by this period. Analysis of the
materials helps to presume the existence of Greek ethnic component among the Late Scythian population at the early stage
of development of Bulhanak hillfort.
Also there are some grounds to assume that Tauric Chersonesos participated in the
foundation and life of this fortification.